Gestational exposure to continuous light impairs the development of the female reproductive system in adult Wistar rat offspring - Ogo, Fernanda Mithie; Siervo, Glaucia Eloisa Munhoz Lion; Praxedes, Ana Maria; Vieira, Henrique Rodrigues; da Silva Scarton, Suellen Ribeiro; Bitencourt, Ana Tereza Guimarães; Arena, Arielle Cristina [UNESP]; Simão, Andréa Name Colado; Guerra, Marina Trevizan; de Freitas Mathias, Paulo Cesar; Fernandes, Glaura Scantamburlo Alves (Wiley, 2023)
Introduction: It has been suggested that maternal exposure to constant light during the gestational period could be considered as a chronic stressor, impairing offspring development by interfering in neuroendocrine and behavior responses. Objective: This study aimed to evaluate whether maternal exposure to continuous light during pregnancy affects the adult reproductive system in the female offspring. Materials and Methods: Pregnant Wistar rats were allocated into light–dark (LD) group, exposed to light and dark photoperiod during gestation, and the light–light (LL) group, exposed to a photoperiod of constant light during gestation. After birth, pups were maintained under normal light–dark photoperiod until adulthood. At postnatal day 90, blood was collected from the female offspring, to analyze plasma luteinizing hormone (LH) and progesterone levels, and the uterus and ovaries were harvested for morphometric, histological, and oxidative stress evaluations. Results and Discussion: Female exposure to continuous light during the intrauterine period resulted in the adult reduction of LH and increased progesterone plasma levels, and uterine injuries a higher number of endometrial glands and reduced levels of antioxidant enzymes, such as glutathione reductase and glutathione S-transferase. In these experimental conditions, gestational continuous light exposure disturbs sex hormone balance and reduces the antioxidant enzymatic activity in the uterus of female offspring in adult life.
Keywords: continuous light; female reproductive development; gestation; oxidative stress; progesterone